Kedudukan Hukum Pergantian Kepala Daerah Terhadap Pemutusan Hubungan Kerja pada Tenaga Honorer di Sekretariat DPRD Kabupaten Serdang Bedagai - Fahriza Fajar; Adawiyah Nasution (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Honorary staff are people appointed by civil service officials within local government agencies to assist with the duties of the State Civil Apparatus so that their obligations are the same and their income comes from the APBD. Honorary staff are employees who work in government agencies but are not included in the State Civil Service. Honorary workers have not been appointed as permanent employees and still receive payment for their services in the form of an honorarium, not a salary. Regional heads include the Governor, Mayor and Regent as well as the DPRD as regional head partners. This research was conducted using normative juridical research methods. The data collection methods used by the author are interviews and literature study. Interviews are data collection techniques carried out face to face and direct question and answer between researchers and sources, while literature studies are data processing carried out by systematizing written legal materials using a regulatory and case approach. The results of this research show that honorary staff often experience injustice at work. This is indicated by the termination of employment relations by regional heads as happened at the Serdang Bedagai Regency DPRD Secretariat agency. Honorary workers have legal status and protection as regulated in Law Number 20 of 2023. The implementation of this research is that the Government needs to create and implement clear regulations to protect the rights of honorary workers.